Effect of ischemic preconditioning on acute recovery in elite judo athletes: a randomized, single-blind, crossover trial - Ceylan, B.; Taskin, H. B.; Šimenko, J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The ischemic preconditioning (IPC) method has been shown to aid the recovery processes; however, no studies have been done to assess its acute recovery use in judo. This study aimed to examine IPC of lower limbs effects on recovery after a judo-specific performance in highly trained male judokas and its applicability during a competition day.